Perancangan Ulang Interior Sumedang Creative Center Dengan Pendekatan Aktivitas - Khairunnisa Sunjaya, Ridha; Cardiah, Tita; Septony Siregar, Fernando (eProceedings of Art & Design, 2024)
Indonesia has shown significant growth in its creative economy. The Sumedang Creative Center was established to support the development of the creative economy in the region. However, there are challenges such as limited facilities, spaces that do not align with users' activities, and suboptimal space conditioning. The goal of redesigning the center's interior is to create an environment that fosters creativity, provides facilities and spaces that meet the needs of creative individuals, and enhances user comfort and productivity. The study used qualitative and quantitative methods, including interviews, surveys, questionnaires, direct observation, and literature review, to gather data. The results indicated that the redesign successfully improves user efficiency and comfort through a design that focuses on users' needs and activities. Keywords: interior, creative center, sumedang